Pengungkapan Nilai Budaya dalam Naskah Drama “RT Nol RW Nol” karya Iwan Simatupang - Zumala’in Nuriyasari; Binti Tsaniatul Wakhidah; Selfi Ananda Putri; Mohammad Kanzunnudin (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Drama as a literary work does not merely present plot and conflicts but also reflects the cultural values embedded within a society. The script RT Nol RW Nol by Iwan Simatupang portrays the life of a marginalized community living under a bridge, facing severe social, economic, and physical limitations. This study aims to reveal the cultural values expressed in the drama and examine how these values are internalized through dialogue, character interactions, and the social dynamics developed throughout the narrative. This research employs a descriptive qualitative method with a cultural value approach. Data were collected using reading and note-taking techniques on selected excerpts of the drama, then analyzed through descriptive and interpretative procedures to uncover the cultural meaning embedded within the characters’ actions and dialogues. The findings show that the script contains material, vital, and spiritual values that represent the identity and social reality of impoverished communities. These values are manifested through depictions of economic hardship, solidarity among characters, and internal reflections that serve as their mental resilience. Additionally, the values of truth, aesthetics, morality, and religiosity enrich the cultural representation found in the drama. The study concludes that drama functions as a reflective medium that illustrates cultural values and serves as an educational tool for understanding the existence and social dynamics of marginalized communities within the Indonesian context.